Análise de imagens na fenotipagem do tamanho e forma de grãos de cultivares de feijoeiro - Cardoso, Everton da Silva (2022)
The common bean (Phaseolus vulgaris L.) is a species that presents enormous variability in the appearance of the grains, mainly about the color, brightness, size and shape. These particularities are highly valued by the consumer market and determine the acceptance of a new cultivar. The carioca grain type is the most cultivated and consumed in the country and, for this reason, it is the type of grain that breeding programs have been most dedicated to the development of new cultivars. Today, growers, consumers and the industry looking for carioca beans with a light cream background color and late browning, light brown stripes, lack of shine in their tegument and weight of 100 grains around 25 grams. The evaluation of the size and shape of the grains has been carried out with the aid of digital calipers or through visual notes, taking into account general aspects of the grains, not only the size and shape in isolation. Although this methodology is precise and accurate, it requires a large amount of time to be performed since a representative sample of grains of each genotype must be measured with a caliper. Due to the longer time required for this evaluation, many of the works in this direction are carried out without repetition or are limited to evaluating a small number of genotypes or grains per genotype. Phenotyping for grain size and shape through images is an alternative, as it allows the evaluation of a large number of grains in a shorter time. Therefore, the objective of this work is to validate this methodology and the Groundeye equipment for image phenotyping of the size and shape of common bean grains. For this, characteristics regarding the grain size of common bean cultivars from the carioca commercial group were measured through image phenotyping and also using a caliper. The two methodologies were compared in terms of experimental precision, accuracy, cultivar discrimination capacity and ranking. Image phenotyping of the size and shape of bean grains, in addition to adding speed and allowing measurements of a large amount of grains and a high number of genotypes to be extracted, is as precise and accurate as the evaluation performed with the use of a caliper and, therefore, can be used routinely by common bean breeding programs.